Rapid regulated dense-core vesicle exocytosis requires the CAPS protein - Rupnik, M. (The National Academy of Sciences, 2000)
Although many proteins essential for regulated neurotransmitter and peptide hormone secretion have been identified, little is understood about their precise roles at specific stages of the multistep pathway of exocytosis. To study the function of CAPS (Ca(2+)-dependent activator protein for secretion), a protein required for Ca(2+)-dependent exocytosis of dense-core vesicles, secretory responses in single rat melanotrophs were monitored by patch-clamp membrane capacitance measurements. Flash photolysis of caged Ca(2+) elicited biphasic capacitance increases consisting of rapid and slow components with distinct Ca(2+) dependencies. A threshold of ≈10 μM Ca(2+) was required to trigger the slow component, while the rapid capacitance increase was recorded already at a intracellular Ca(2+) activity < 10 μM. Both kinetic membrane capacitance components were abolished by botulinum neurotoxin B or E treatment, suggesting involvement of SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor)-dependent vesicle fusion. The rapid but not the slow component was inhibited by CAPS antibody. These results were further clarified by immunocytochemical studies that revealed that CAPS was present on only a subset of dense-core vesicles. Overall, the results indicate that dense-core vesicle exocytosis in melanotrophs occurs by two parallel pathways. The faster pathway exhibits high sensitivity to Ca(2+) and requires the presence of CAPS, which appears to act at a late stage in the secretory pathway.